Nicotinamide Improves Cognitive Function in Mice With Chronic Cerebral Hypoperfusion - Liu, Bin; Zhao, Guifeng; Jin, Ling; Shi, Jingping (Frontiers in Neurology, 2021)
Normal brain function requires steady blood supply to maintain stable energy state. When blood supply to the brain becomes suboptimal for a long period of time, chronic cerebral hypoperfusion (CCH) and a variety of brain changes may occur. CCH causes white matter injury and cognitive impairment. The present study investigated the effect of nicotinamide (NAM) on CCH-induced cognitive impairment and white matter damage in mice. Male C57Bl/6J mice aged 10 - 12 weeks (mean age = 11 ± 1 weeks) and weighing 24 - 29 g (mean weight = 26.5 ± 2.5 g) were randomly assigned to 3 groups (8 mice/group): sham group, CCH group and NAM group. Chronic cerebral hypoperfusion (CCH) was induced using standard methods. The treatment group mice received intraperitoneal injection of NAM at a dose of 200 mg/kg body weight (bwt) daily for 30 days. Learning, memory, anxiety, and depression-like behaviors were measured using Morris water maze test (MWMT), open field test (OFT), sucrose preference test (SPT), and forced swim test (FST), respectively. White matter damage and remodeling were determined via histological/ immunohistochemical analyses, and western blotting, respectively. The results showed that the time spent in target quadrant, number of crossings and escape latency were significantly lower in CCH group than in sham group, but they were significantly increased by NAM (p < 0.05). Mice in NAM group moved significantly faster and covered longer distances, when compared with those in CCH group (p < 0.05). The percentage of time spent in open arms and the number of entries to the open arms were significantly lower in CCH group than in NAM group (p < 0.05). Moreover, anhedonia and histologic scores (index of myelin injury) were significantly higher in CCH group than in sham group, but they were significantly reduced by NAM (p < 0.05). The results of immunohistochemical staining and Western blotting showed that the protein expressions of 2', 3'-cyclic-nucleotide 3'-phosphodiesterase (CNPase) and synaptophysin were significantly downregulated in CCH group, relative to sham group, but they were significantly upregulated by NAM (p < 0.05). These results indicate that NAM improves cognitive function in mice with CCH.